2006
DOI: 10.1111/j.1601-183x.2006.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

A hitchhiker's guide to behavioral analysis in laboratory rodents

Abstract: Genes and environment are both essential and interdependent determinants of behavioral responses. Behavioral genetics focuses on the role of genes on behavior. In this article, we aim to provide a succinct, but comprehensive, overview of the different means through which behavioral analysis may be performed in rodents. We give general recommendations for planning and performing behavioral experiments in rats and mice, followed by brief descriptions of experimental paradigms most commonly used for the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 133 publications
3
171
0
1
Order By: Relevance
“…36,54 Footprint gait assesses walking patterns and has been used to evaluate movements and motor coordination in rodents, providing information on cerebellar function. 40,56,57 In this study the mice did not show abnormalities in the walking patterns as a consequence of the marking procedure when compared with control animals.…”
Section: Evaluation Of Adult Behaviour and Wellbeing: Impact Of Indivmentioning
confidence: 75%
See 2 more Smart Citations
“…36,54 Footprint gait assesses walking patterns and has been used to evaluate movements and motor coordination in rodents, providing information on cerebellar function. 40,56,57 In this study the mice did not show abnormalities in the walking patterns as a consequence of the marking procedure when compared with control animals.…”
Section: Evaluation Of Adult Behaviour and Wellbeing: Impact Of Indivmentioning
confidence: 75%
“…The rotarod test, measuring locomotor function and coordination, 35,40,44,56,57 confirmed that there were no major differences in the locomotion abilities of individually identified animals except in a particular constant velocity test, at 15 rpm, in which Toe ink females presented a shorter latency time to fall off from the moving rod, but the same was not detected in males. Moreover, when using an accelerating rod (0.6 rpm/s), no differences could be detected between the different groups.…”
Section: Evaluation Of Adult Behaviour and Wellbeing: Impact Of Indivmentioning
confidence: 85%
See 1 more Smart Citation
“…Both paradigms are used for measuring state anxiety that is based on the conflict between exploration of novel environments and the avoidance of potentially dangerous situations (Hogg, 1996;Rodgers and Dalvi, 1997;Hascoet et al, 2001;Millan et al, 2003;de Sousa et al, 2006). TRPV1-KO much faster adapted to the aversive light compartment, spent more time in the light compartment in the light-dark test, and explored the open arms of the elevated plus maze more intensively than their wild-type littermates, indicating that they are less anxious.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the anatomical and genetic background of these two kinds of memory is not the same (Kandel, 2001;Kandel, 2009). The interplay of environmental and genetic factors (Sousa, Almeida & Wotjak, 2006;Wahlsten, Metten, Phillips, et al, 2003) and related differences in brain wiring and biochemistry result in individual but also between-strain variations in learning and memory abilities commonly observed in random human or animal populations (Gökçek-Saraç, Karakurt, Adalı & Jakubowska-Doğru, 2012; Gökçek-Saraç, Adalı & Jakubowska-Doğru, 2013; Jakubowska-Doğru, Gümüşbaş & Kara, 2002). Non-cognitive factors such as sensory perception, emotionality, or locomotor activity may also contribute to this variation.…”
Section: Introductionmentioning
confidence: 99%